A ROBUST STABILITY TEST FOR BIMODAL SYSTEMS - Eren, Yavuz; Gorgun, Haluk (YILDIZ TECHNICAL UNIV, 2016)
This paper studies robust stability problem for bimodal systems with continuous vector field. Firstly, a corollary is presented to construct common quadratic Lyapunov function to check the robust stability of the related system with norm-bounded uncertainties. Then, a mechanical system in bimodal configuration is provided and the switching mechanism of the system is simulated with nominal and norm-bounded uncertain parameters. The effectiveness of the study is demonstrated with simulation studies on spring-mass-damper system.
Keywords: Bimodal systems; norm-bounded uncertainty; robust stability; QUADRATIC LYAPUNOV FUNCTIONS; PIECEWISE; STABILIZATION; Engineering